Comparison Sunscreen Potential of Extract with Ethanol Extract Cream of Basil Leaves (Ocimum basilicum var. anisatum Benth) In Vitro - Juliadi, Debby (E-Jurnal Medika Udayana; Vol 13 No 5 (2024): E-Jurnal Medika Udayana, 2024)
Sunscreens on the market are generally made of synthetic materials. However, many synthetic active substances can cause allergies and irritation. Along with the trend back to nature, the use of traditional medicine among the public is more in demand. Natural ingredients that have potential for sunscreen are basil leaves (Ocimum basilicum var. anisatum Benth). Cream preparations have the advantage of a fairly high aesthetic value and the level of comfort in use is quite good. This study aims to determine the sunscreen potency of the extract and cream of the ethanolic extract of basil leaves in vitro based on the values of %Te, %Tp and SPF. Determination of sunscreen potency was carried out by calculating %Te, %Tp and SPF values on ethanol extract of basil leaves and cream of ethanolic extract of basil leaves in vitro using UV-Vis spectrophotometry at a wavelength of 290-400 nm every 5 nm interval. The %Te value of basil leaf ethanol extract at a concentration of 100 ppm was not included in the category, at a concentration of 200 ppm and 300 ppm it was in the category of extra protection. And the value of %Te cream of basil leaf ethanol extract at a concentration of 100 ppm is not included in the category, at a concentration of 200 ppm it is in the regular suntan category, at a concentration of 300 ppm it is in the extra protection category. The %Tp value of ethanol extract of basil leaves and cream of ethanolic extract of basil leaves was included in the total block category. The SPF value of the ethanolic extract of basil leaves at concentrations of 100 ppm, 200 ppm and 300 ppm, respectively, is 3.873 (minimum); 12,163(maximum); and 40,736(ultra). While the SPF value of the cream of ethanol extract of basil leaves was 2.792 (minimum); 6,508(extra); and 12,259 (maximum).